2023
DOI: 10.1108/jiabr-08-2022-0220
|View full text |Cite
|
Sign up to set email alerts
|

The motivating factors for switching intention to use halal cosmetics in Indonesia

Abstract: Purpose The halal cosmetics industry continues to grow significantly. Furthermore, using halal cosmetics is a must for Muslims. This study aims to analyze the factors influencing the switching intention to halal cosmetics in Indonesia. Design/methodology/approach This quantitative study uses a Partial Least Square-Structural Equation Modelling (PLS-SEM) on 214 respondents. The variables include halal certification, halal awareness, product image, perceived behavioral control, subjective norm, attitude, adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
0
0
0
1
Order By: Relevance
“…Further, the presence of halal awareness among Muslim costumers motivates their preference for buying and consuming halal products due to the belief that their consumption is on halal products is obligatory. This inclination stems from the desire to avoid the consumption of haram products and subsequently pushed the transition from non-halal to halal consumptions (Wisudanto et al, 2023).…”
Section: Halal Literacy and Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the presence of halal awareness among Muslim costumers motivates their preference for buying and consuming halal products due to the belief that their consumption is on halal products is obligatory. This inclination stems from the desire to avoid the consumption of haram products and subsequently pushed the transition from non-halal to halal consumptions (Wisudanto et al, 2023).…”
Section: Halal Literacy and Awarenessmentioning
confidence: 99%
“…In addition to this, a significant portion of scholarly investigation is dedicated to the examination of the significance of halal literacy and awareness in shaping consumer intentions towards the purchase and consumption of halal products. This topic has been explored by various researchers, including Kasri et al, (2023), Wisudanto et al, (2023), Maryam and Sumar' in (2022), Mardhiyah, Mawardi, Widiastuti, Mustofa, Abdullah, Sinulingga, Saptowati Mutmainah (2018), andYunus et al, (2014), Ab Talib and Wahab (2021), Ab Talib and Zulfakar (2023), Al-shami andAbdullah (2023), andZiegler et al, (2022).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Having halal certification brings some benefits to Wardah cosmetics, including increasing customer confidence in the product, ensuring the customers feel secured because halal-certified goods are ensured to be safe and halal. Therefore, it might drive the customers to shift from non-halal to halal products (Wisudanto et al, 2023). Based on Table 1 above, it is shown that the cosmetic industry is potential to grow in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Halal alah sat keyakinan agama (Wisudanto et al, 2023). Halal telah berkembang menjadi aspek penting dalam perdagangan dan industri.…”
unclassified